Proposed digital scanning parameters for digital masters of still photographs - Codamon, Kevin Constantine A.; Quiros, Edgardo B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2002)
The creation of a digital master preserves the most information captured from a physical source. Derivative images for purposes such as on screen display, image databases and online libraries can be then extracted from the digital master. The process of converting physical photographs to a digital form requires uniform scanning parameters in order for it to become efficient without sacrificing quality. With this in mind, what are the steps to be taken in order to come up with scanning parameters for digital masters of still photographs?
Photograph collections form the Marine Science Institute library in UP Diliman and the Filipiniana Serials/Special collection of UP Main Library were surveyed to approximate the types of photograph types found in a library. The only variety that was noted was the range of color information, with all the photographs Within the normal 8.5 by 11.5 physical dimensions, and can be categorized as color, black and white and sepia tone.
Proposed scanning parameters for black and white still photographs are: a) grayscale scanning, b) 8 bit color depth and c) uncompressed TIFF (Tagged Image File Format) while parameters for sepia and color photographs are: a) color scanning, b) 24 bit color depth and c) uncompressed TIFF.
Scanning parameters chosen were the settings used by the different digital imaging projects, these parameters are: scanning type, bit depth, resolution, file format and compression.
Although specific scanning parameters have been proposed in this study, these same parameters are dictated by the current technology available; that said, it is important for institutions or individuals planning to do their own project to incorporate new methods and practices that may surpass the effectiveness of the techniques proposed.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Photography -- Digital techniques; Image processing -- Digital techniques